The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.17523/bia.2018.v75.e1419
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade e características agronômicas de Brachiaria brizantha cv. Paiaguás submetida a doses de nitrogênio sob cortes

Abstract: Objetivou-se descrever a resposta da Brachiaria brizantha cv. Paiaguás em doses de adubação nitrogenada no segundo ano de produção. O experimento foi conduzido na área experimental da Universidade do Estado de Mato Grosso, localizada no município de Tangará da Serra, em blocos casualizados, com seis tratamentos (doses de 0, 50, 100, 150, 200 e 250 kg/ha de N) e quatro repetições, em parcelas de 9 m² cada. As doses foram parceladas em quatro vezes, aplicadas após cada corte. Observouse efeito significativo (P<0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 13 publications
2
7
0
5
Order By: Relevance
“…They showed that accumulated production before four cuts at the higher dose yielded the maximum production of 23,200.00 kg ha -1 DM. In the present study, during the 1st cycle, a greater yield of 21,061.69 kg was obtained with 328 kg ha -1 N. Therefore, similar results were obtained, although the tests occurred in different geographic regions and with different sources of N. Germano et al (2018) and Froehlich et al (2019), who also tested Paiaguás palisade grass in Red Oxisol soil, observed a linear response in DM yield up to 250 kg ha -1 of N, which was the maximum rate of N tested. Productivity was from 5,860.00 to 8,127.00 kg ha -1 of DM, respectively.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…They showed that accumulated production before four cuts at the higher dose yielded the maximum production of 23,200.00 kg ha -1 DM. In the present study, during the 1st cycle, a greater yield of 21,061.69 kg was obtained with 328 kg ha -1 N. Therefore, similar results were obtained, although the tests occurred in different geographic regions and with different sources of N. Germano et al (2018) and Froehlich et al (2019), who also tested Paiaguás palisade grass in Red Oxisol soil, observed a linear response in DM yield up to 250 kg ha -1 of N, which was the maximum rate of N tested. Productivity was from 5,860.00 to 8,127.00 kg ha -1 of DM, respectively.…”
Section: Resultssupporting
confidence: 86%
“…In the first cycle, the N rates that provided the greatest density of tillers the 1st (p<0.01), 2nd (p<0.01), 3rd (p<0.05), and 4th (p<0.01) growth periods were 116, 159, 173, and 253 kg N ha -1 , respectively. Regarding Paiaguás palisade grass height Germano et al (2018) on Dystrophic Oxysoil, N rates between 0 to 250 kg ha -1 were evaluated and they observed quadratic responses with the greatest height of 0.59 m using 210 kg ha -1 . Froehlich et al (2019) using the same soil, grass, and N rate, observed a greater height of 0.63 m 150 kg ha -1 of N. Bezerra et al (2019) using Paiaguás palisade grass in the Mato Grosso state region obtained heights between 53.55 and 55.48 cm at 30 and 60 d after sprouting during tests using wood ash as a fertilizer in soils under water stress.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Basilisk has, on average, 10 to 11 live leaves per tiller, while cv. Xaraés has approximately 3 to 4 live leaves per tiller (Galzerano, Malheiros, Raposo, Morgado, & Ruggieri, 2013), and cvs Marandu, Paiaguás and Piatã possess, on average, 4 to 5 leaves per tiller (Casagrande et al, 2010;Orrico Júnior, Centurion, Sunada, & Vargas Júnior 2013;Germano, Vendruscolo, Daniel, & Dalbianco 2018). Leaf appearance rate (LAR, cm tiller -1 day -1 ), leaf elongation rate (LER, cm tiller -1 day -1 ), stem elongation rate (SER, cm tiller -1 day -1 ), leaf senescence rate (LSR, cm tiller -1 day -1 ), leaf lifespan (LLS, days), final leaf length (FLL, cm), number of live leaves (NLL), herbage mass (HM, kg ha -1 ), leaf mass (LM, kg ha -1 ), stem mass (SM, kg ha -1 ), dead material mass (DMM, kg ha -1 ), undesirable-plant mass (UPM, kg ha -1 ), leaf:stem ratio (L:S).…”
Section: Morphogenetic and Structural Variablesmentioning
confidence: 99%
“…Em estudos com Brachiaria brizantha cv. Paiaguás, adubada com diferentes doses de nitrogênio, avaliando quatro cortes,Germano et al (2018) verificaram efeito das doses de nitrogênio na produção de massa seca, sendo que a relação folha:colmo não foi influenciada significativamente nos cortes avaliados, bem como no somatório dos quatro cortes avaliados juntos.Dougherty e Rhykerd (1985) afirmam que é de fundamental importância o estudo da eficiência da utilização do nitrogênio em sistemas produtivos, onde as quantidades de nitrogênio aplicadas ultrapassam a capacidade que as plantas têm de absorver esse nutriente, pois o mesmo pode ser lixiviado e acumular-se nos tecidos, reduzindo sua eficiência de aproveitamento pelas plantas e não trazendo os benefícios esperados.De acordo comSilva et al (2013), a resposta da pastagem à aplicação de fertilizantes nitrogenados em uma região específica, depende principalmente do suprimento de nitrogênio no solo e das condições climáticas.…”
unclassified